Dualistic roles and mechanistic insights of macrophage migration inhibitory factor in brain injury and neurodegenerative diseases. Issue 3 (March 2023) - Xuan, Wei; Xie, Wanqing; Li, Fengshi; Huang, Dan; Zhu, Ziyu; Lin, Yuxuan; Lu, Binwei; Yu, Weifeng; Li, Yan; Li, Peiying
Macrophage migration inhibitory factor (MIF) is involved in various immune-mediated pathologies and regulates both innate and adaptive immune reactions, thus being related to several acute and chronic inflammatory diseases such as rheumatoid arthritis, septic shock, and atherosclerosis. Its role in acute and chronic brain pathologies, such as stroke and neurodegenerative diseases, has attracted increasing attention in recent years. In response to stimuli like hypoxia, inflammation or infection, different cell types can rapidly release MIF, including immune cells, endothelial cells, and neuron cells. Notably, clinical data from past decades also suggested a possible link between serum MIF levels and the severity of stroke and the evolving of neurodegenerative diseases. In this review, we summarize the major and recent findings focusing on the mechanisms of MIF modulating functions in brain injury and neurodegenerative diseases, which may provide important therapeutic targets meriting further investigation.